Bacteriological Study of Eye infection in Baghdad City (Medico Legal Update, 2020)
The present study included 250 clinical samples during the period between December 2018 – April 2019 on250 patients with ophthalmological infections of both sexes & different ages ( 3 days - 75 years old) , attendto ophthalmological clinic in hospital Ibn-AL-Hythem for eyes infection in Baghdad. The ophthalmologicalinfections classified into 3 types according to the anatomical site of involvement. The first group wasconjunctivitis(200)case, the 2nd was Blepharitis (35) case & the 3rd was Keratitis ( 15) cases. Isolation ofthe causative micro-organisms for the previous infections, culture & sensitivity test to different antimicrobialagents were done. The results showed that 200(229.4 )% are you giren significant growth of bacteriawhile 50(69.07% ) were no growth for bacteria . Include Staphylococcus aureus(77.6%),Staphylococcus epidermidis (13.6%) , Streptococcus pneumonia(6.4%) & Streptococcus pyogenes(2.1%) , while G-ve isolates61(30.5%) include (7) species of bacteria ; Haemophilus influenzae(81.9%), Klebsiella pneumonia(6.5%), Proteus spp & Pseudomonas aeruginosa, the Same (3.2%) for each & finally Neisseria gonorrhoeae,Moraxella spp, Acinetobacter were the least(1.6%) for each. Antimicrobial (12 agents) susceptibility of thebacterial isolates revealed marked resistant of these isolates for most antimicrobial agents e.g. Penicillin(87.8%),amoxicillin/clavulanicacid(84.4%),cephalexien(83.9%),erythromycin(83.4%), ampicillin (71.3%)while the least resistant(8.2%) reported for ciprofloxacin.